HUBUNGAN FUNGSI KOGNITIF DENGAN KUALITAS HIDUP PADA LANSIA - Juan Stuart; Meiyanti (MEDIA ILMU KESEHATAN, 2020)
Background: The aging process could cause physical changes and lowered organ function. These changescan affect the quality of life of the elderly, such as impaired cognitive function. It was found that there are pros and cons of whether or not thecognitive function have relates with quality of life of the elderly. Objective: To know the relationship between cognitive function and quality of life. Methods: This research is a descriptive study of analytic with crosssectional design with the number of respondents as many as 124 elderly, aged ≥ 60 years in Panti sosial tresna werdha 4 Cengkareng, West Jakarta. By using MMSE questionnaire to assess cognitive function and WHOQOL-BREF for quality of life. Results:Respondents were most acquired aged 60-74 years (81.5%), female gender (59.7%), as well as the level of education under high School (79.8%). The results of the study of the relationship test between cognitive function and quality of life is p=0.003 in the physical aspect, p=0.000 in psychological, p=0.004 in social and p=0.002 in the environmental aspects of the quality of life. Conclusion: Cognitive function affects all aspects of quality of life in elderly.